A four-year observational study to examine the dietary impact of the North Carolina Healthy Food Small Retailer Program, 2017–2020 - Jilcott Pitts, Stephanie B. (Int J Behav Nutr Phys Act, 2021)
BACKGROUND: The North Carolina (NC) Healthy Food Small Retailer Program (HFSRP) was passed into law with a $250,000 appropriation (2016–2018) providing up to $25,000 in funding to small food stores for equipment to stock healthier foods and beverages. This paper describes an observational natural experiment documenting the impact of the HFSRP on store food environments, customers’ purchases and diets. METHODS: Using store observations and intercept surveys from cross-sectional, convenience customer samples (1261 customers in 22 stores, 2017–2020; 499 customers in 7 HFSRP stores, and 762 customers in 15 Comparison stores), we examined differences between HFSRP and comparison stores regarding: (1) change in store-level availability, quality, and price of healthy foods/beverages; (2) change in healthfulness of observed food and beverage purchases (“bag checks”); and, (3) change in self-reported and objectively-measured (Veggie Meter®-assessed skin carotenoids) customer dietary behaviors. Differences (HFSRP vs. comparison stores) in store-level Healthy Food Supply (HFS) and Healthy Eating Index-2010 scores were assessed using repeated measure ANOVA. Intervention effects on diet were assessed using difference-in-difference models including propensity scores. RESULTS: There were improvements in store-level supply of healthier foods/beverages within 1 year of program implementation (0 vs. 1–12 month HFS scores; p = 0.055) among HFSRP stores only. Comparing 2019 to 2017 (baseline), HFSRP stores’ HFS increased, but decreased in comparison stores (p = 0.031). Findings indicated a borderline significant effect of the intervention on self-reported fruit and vegetable intake (servings/day), though in the opposite direction expected, such that fruit and vegetable intake increased more among comparison store than HFSRP store customers (p = 0.05). There was no significant change in Veggie Meter®-assessed fruit and vegetable intake by customers shopping at the intervention versus comparison stores. CONCLUSIONS: Despite improvement in healthy food availability, there was a lack of apparent impact on dietary behaviors related to the HFSRP, which could be due to intervention dose or inadequate statistical power due to the serial cross-sectional study design. It may also be that individuals buy most of their food at larger stores; thus, small store interventions may have limited impact on overall eating patterns. Future healthy retail policies should consider how to increase intervention dose to include more product marketing, consumer messaging, and technical assistance for store owners.